The Effect of Cultural Factors, Price, and Promotion on Purchasing Decisions - Alberta Theresia Rene; Florida Mini; Fransiska Irma Fardina (Yayasan Az Zukhruf Cendikia, 2025)
Abstract Purpose – This study aims to examine the influence of cultural factors, price, and promotion on purchasing decisions. Design/methodology/approach – This research uses a quantitative approach. It was conducted using a questionnaire distributed to people in East Nusa Tenggara, especially in the Regency, with as many as 80 distributed via social media. Each questionnaire contained 76 statements for respondents to answer. To get the result of this research, I used PLS-SEM Version 3.0 Findings – Research limitations/implications – The findings reveal that culture has a positive and significant effect on purchasing decisions, price has a positive but insignificant effect on purchasing and promotion has a positive and significant effect on purchasing decisions. Each questionnaire contained 76 statements for respondents to answer. Research limitations/implications- This study introduces needs variables in purchasing decisions, especially experience and attitude, which provide new insight. However, the findings are limited to consumer behavior and product marketing, requiring further research.